Age-Related Effects on Cognitive-Locomotor Dual-Task Abilities in Activities Representative of Daily Life Among Young Seniors. - Deblock-Bellamy, Anne; Lamontagne, Anouk; McFadyen, Bradford J.; Ouellet, Marie-Christine; Blanchette, Andreanne K. (Perceptual & Motor Skills, 2025)
Objective: This study examined whether dual-task (DT) cognitive-locomotor interferences are present among young seniors (55–75 years) simultaneously performing a locomotor and a cognitive task of varying levels of complexity while ambulating in a virtual community environment. Method: To assess DT abilities, participants were asked to walk down a virtual mall corridor while remembering a 5-item shopping list. Two levels of complexity for the locomotor (without vs. with obstacles) and the cognitive task (unmodified vs. modified shopping list) were assessed. After measuring the presence of locomotor and cognitive DT costs (DTC) using one sample Wilcoxon signed-rank tests, a nonparametric ANOVA was performed to explore the impact of task complexity on DTC. Spearman coefficients were used to examine the impact of age on DTC. Results: Sixteen participants were recruited. Locomotor and cognitive DTC were observed in all DT conditions, except the easiest combination (no obstacle + unmodified shopping list). These DTC were mainly impacted by the complexity of the cognitive task. They were also positively correlated to age. Discussion: The results highlight the importance of real-life scenarios for accurately describing DT abilities for whom locomotor DTC seems to increase with age despite the absence of daily limitations.